2014
DOI: 10.1007/s10828-014-9067-5
|View full text |Cite
|
Sign up to set email alerts
|

Middle Dutch back vowels in rhymes

Abstract: Dutch underwent many changes in its vowel system in the course of its history. One way of exploring the phonology of the vocalic system at an earlier period of the language is to examine rhymes. The rhyming verse which is used in the moral didactic text of Ms. Marshall 29 offered an excellent opportunity to not only establish the differences between Modern and Middle Dutch, but also to trace any variation in the transition period from early to late Middle Dutch. We focused on rounded vowels, which were indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…We first examine Mellibeus and Saladijn , whose spelling is very similar to ModD. Each text is written in a different hand but both show consistency in their spelling (Sytsema et al 2014). 11 The only variation that occurs across the texts is confined to the orthography of a specific vowel in closed syllables, namely, the descendent of PGmc † /au/, which is written as <oe> in Mellibeus but as <oo> in Saladijn .…”
Section: Spelling Evidencementioning
confidence: 99%
See 3 more Smart Citations
“…We first examine Mellibeus and Saladijn , whose spelling is very similar to ModD. Each text is written in a different hand but both show consistency in their spelling (Sytsema et al 2014). 11 The only variation that occurs across the texts is confined to the orthography of a specific vowel in closed syllables, namely, the descendent of PGmc † /au/, which is written as <oe> in Mellibeus but as <oo> in Saladijn .…”
Section: Spelling Evidencementioning
confidence: 99%
“…To obtain evidence from rhyme we had to distinguish between rounded and unrounded vowels. Sytsema et al (2014) have shown that round vowels of the same PGmc origin rhyme in Saladijn and Mellibeus even if they are spelt differently (see tables 13 and 14), whereas vowels of different origins do not appear in rhyming pairs even if they are spelt the same (see table 14). Descendants of PGmc † /ō/ are consistently spelt <oe>, whereas descendants of PGmc † /au/ could be spelt <oe> or <oo>.…”
Section: Evidence From Rhymementioning
confidence: 99%
See 2 more Smart Citations
“…The text is written in littera textualis in two columns of 48 lines each and is written by two regular hands (Sytsema et al. : 158). The Lutgart manuscript is kept in Copenhagen and dates back to around 1300.…”
Section: Introductionmentioning
confidence: 99%